Responses of black soybean to rice husk-derived bio-silica nanoparticles and mycorrhiza on physiology and root development under drought stress - DWI SUCI LESTARIANA; EDI PURWANTO; MUJI RAHAYU; SUPRIYONO SUPRIYONO (Society for Indonesian Biodiversity, 2025)
Abstract. Lestariana DS, Purwanto E, Rahayu M, Supriyono. 2025. Responses of black soybean to rice husk-derived bio-silica nanoparticles and mycorrhiza on physiology and root development under drought stress. Biodiversitas 26: 5824-5837. This study investigated the combined effects of rice husk-derived bio-silica nanoparticles and Arbuscular Mycorrhizal Fungi (AMF) on the physiological and root development responses of two contrasting black soybean (Glycine max) cultivars, Malika and Detam 2. A factorial experiment was arranged in a completely randomized design with three replicates. Treatment included two cultivars (Malika, Detam 2), AMF (inoculated, non-inoculated), and five biosilica nanoparticle concentrations (0, 50, 100, 150, 200 ppm). Data were analyzed using ANOVA, and mean differences were compared with Duncan's Multiple Range Test (DMRT). Results showed that cultivar Malika maintained 0.72% (p<0.05) lower H?O? accumulation and stronger antioxidant activity, while cultivar Detam 2 exhibited better root development when treated with 150-200 ppm biosilica nanoparticle and combined with AMF inoculation, showing the longest length (37 cm; p<0.05) and the greatest volume (3.17 cm³; p<0.05). These improvements indicate that bio silica nanoparticles supported redox stability and osmotic regulation, while AMF strengthened nutrient acquisition and root elongation. Overall, the integrated application of AMF and bio silica nanoparticles induced complementary biochemical and morphological tolerance mechanisms in both cultivars, enhancing drought resilience through reduced oxidative stress, improved osmotic balance, and strengthened root development. This study provides evidence of synergistic interactions between AMF and rice husk-derived bio-silica nanoparticles in black soybean, offering a sustainable, waste-based strategy to improve legume productivity under dryland and climate-stress conditions.